2010
DOI: 10.1051/0004-6361/200912439
|View full text |Cite
|
Sign up to set email alerts
|

VERA observations of SiO maser emission from R Aquarii

Abstract: Aims. We aim to study the spatial distribution of the v = 1 and v = 2 J = 1−0 SiO maser emission from R Aqr, a well known stellar symbiotic system. In particular, we intend to determine the annual parallax and proper motion of the source by means of measurements of the absolute coordinates of the maser spots. Methods. We performed VLBI observations of the v = 1 and v = 2 J = 1−0 maser emission, at 7 mm wavelength, using VERA. We present observations made in 11 epochs, between December 2004 and October 2006, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 31 publications
5
33
0
Order By: Relevance
“…Observations of SiO maser emission in R Aqr (e.g. Cotton et al 2004;Kamohara et al 2010;Pardo et al 2004) show properties completely similar to those found in standard AGB stars. VLBI maps show, in particular, that the SiO maser in general occupy a ring-like region (with radius ∼5 × 10 13 cm) that is comparable to those typical of AGB stars.…”
Section: Numerical Model Of Line Formationsupporting
confidence: 69%
See 2 more Smart Citations
“…Observations of SiO maser emission in R Aqr (e.g. Cotton et al 2004;Kamohara et al 2010;Pardo et al 2004) show properties completely similar to those found in standard AGB stars. VLBI maps show, in particular, that the SiO maser in general occupy a ring-like region (with radius ∼5 × 10 13 cm) that is comparable to those typical of AGB stars.…”
Section: Numerical Model Of Line Formationsupporting
confidence: 69%
“…SiO maser emission (v > 0 lines at mm wavelengths) in R Aqr is relatively "normal" compared to what is observed in standard AGB stars (e.g. Pardo et al 2004;Cotton et al 2004;Kamohara et al 2010). We recall that SiO maser emission comes from the innermost circumstellar regions, in our case at about 5 × 10 13 cm.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…We have not considered the presence of a companion star in our calculations. This approach is justified because our calculations show that the v = 1, J = 3 − 2 CO line is formed very close to the star (r 3 R ) and maser emission lines formed at similar distances observed towards close binaries AGB stars, such as R Aqr, do not show distinct features from those observed towards single AGB stars (see, e.g., Kamohara et al 2010). We note, however, that the five AGB stars discussed here are peculiar in some way because of interactions with their companions.…”
Section: Modellingmentioning
confidence: 77%
“…The Hipparcos catalog (Perryman & ESA 1997b) gives a value of 211 +71 −42 pc, while Kamohara et al (2010) estimated the distance to 214 +45 −32 pc via maser observations. The mass and luminosity, obtained from modeling and observations, are 1 M and 3470 L , respectively (Hofmann et al 2000).…”
Section: R Aquilaementioning
confidence: 99%